Identification of Rf9, a Gene Contributing to the Genetic Complexity of Fertility Restoration in Hybrid Wheat - Shahinnia, Fahimeh; Geyer, Manuel; Block, Annette; Mohler, Volker; Hartl, Lorenz (Frontiers in Plant Science, 2020)
Wheat (Triticum aestivum L.) is a self-pollinating crop whose hybrids offer the potential to provide a major boost in yield. Male sterility induced by the cytoplasm of Triticum timopheevii is a powerful method for hybrid seed production. Hybrids produced by this method are often partially sterile and full fertility restoration is crucial for wheat production using hybrid cultivars. To identify genetic loci controlling fertility restoration in wheat, we produced two cytoplasmic male-sterile (CMS) backcross (BC1) mapping populations. The restorer lines Gerek 79 and 71R1203 were used to pollinate the male-sterile winter wheat line CMS-Sperber. Seed set and numbers of sterile spikelets per spike were evaluated in 340 and 206 individuals of the populations derived from Gerek 79 and 71R1203, respectively. Genetic maps were constructed using 930 and 994 single nucleotide polymorphism (SNP) markers, spanning 2,160 and 2,328 cM over 21 linkage groups in the two populations, respectively. Twelve quantitative trait loci (QTL) controlled fertility restoration in both BC1 populations, including a novel restorer-of-fertility (Rf) locus flanked by the SNP markers IWB72413 and IWB1550 on chromosome 6AS. The locus was mapped as a qualitative trait in the BC1 Gerek 79 population and was designated Rf9. Hundred-nineteen putative candidate genes were predicted within the QTL region on chromosome 6AS. Among them were genes encoding mitochondrial transcription termination factor and pentatricopeptide repeat-containing proteins that are known to be associated with fertility restoration. This finding is a promising step to better understand the functions of genes for improving fertility restoration in hybrid wheat.